A hybrid method for optimization of frame structures with good constructability. (1st February 2023) - Xu, An; Li, Shumin; Fu, Jiyang; Misra, Anil; Zhao, Ruohong
Highlights: A three-step hybrid optimization method that contains the continuum topology optimization, the transformation process, and size optimization of structural members. A method that transforms the results of continuum topology optimization to frame structures with good constructability. This hybrid method is of high computational efficiency and fully utilizes the advantages of both continuum topology optimization and size optimization. Abstract: Frame structure optimization is a design problem posed to find an optimized structural member layout and the most suitable cross-sectional size according to the design requirements. This study proposes a hybrid optimization method, which integrates the continuum topology optimization, the transformation process, and size optimization to achieve this goal. Firstly, the continuum topology optimization is carried out to get the rough layout of structural members. Then using the method proposed in this paper, the result of continuum topology optimization is transformed into a frame structure which uses only non-curved and prismatic members to ensure ease of constructability. Finally, member sizes of the frame structure are optimized to obtain the optimal design of the structure. The high efficiency of the employed continuum topology methods significantly reduces the computational intensity of this three-step hybrid optimization method compared to that of the commonly-used discrete optimization method. This hybrid method builds a bridge between continuum topology optimization and size optimization of structure members, and has a lot of different application scenarios, such as the optimization of the bracing system of high-rise buildings, or the layout of plane truss structures.